2021
DOI: 10.1080/07256868.2021.1939276
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Atmosphere in Negotiations of Groupness: A Study of a Meeting Place for Older Russian-speaking Migrants

Abstract: While existing literature on third-sector support for ageing migrants shows that social clubs can be a vital source of social support, what remains unclear is how these positive outcomes are attained on an interactional level. Drawing on fieldwork conducted over the course of one year in a meeting place for older Russian-speaking migrants in the capital region of Finland, this paper adopts a processual approach to examine how a sense of groupness is negotiated in the meeting place. The attendees of the meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…Research showed that Russians are not accepted in Finnish society and regarded as an unwelcomed minority group and sometimes, referred to by derogatory terms like 'Ryssä' even when they appear to be White and can speak Finnish (Heikkinen 2011;Tiaynen-Qadir 2020). Stereotypical discrimination against older Russian migrants for their accents is very prevalent (Asikainen 2021). The discrimination that older migrants face in the Finnish society have made them limit their group activities to only Russianspeaking participants (Asikainen 2021;Tiaynen-Qadir 2020).…”
Section: Intersectional Perspective Inadequately Explored In Finnish ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that Russians are not accepted in Finnish society and regarded as an unwelcomed minority group and sometimes, referred to by derogatory terms like 'Ryssä' even when they appear to be White and can speak Finnish (Heikkinen 2011;Tiaynen-Qadir 2020). Stereotypical discrimination against older Russian migrants for their accents is very prevalent (Asikainen 2021). The discrimination that older migrants face in the Finnish society have made them limit their group activities to only Russianspeaking participants (Asikainen 2021;Tiaynen-Qadir 2020).…”
Section: Intersectional Perspective Inadequately Explored In Finnish ...mentioning
confidence: 99%
“…Stereotypical discrimination against older Russian migrants for their accents is very prevalent (Asikainen 2021). The discrimination that older migrants face in the Finnish society have made them limit their group activities to only Russianspeaking participants (Asikainen 2021;Tiaynen-Qadir 2020). Due to discrimination and racism, some older migrants face microaggressions in their everyday lives along with limited opportunities to engage in the Finnish society.…”
Section: Intersectional Perspective Inadequately Explored In Finnish ...mentioning
confidence: 99%